Development cycle of a potential biocontrol agent: the American hoverfly, Eupeodes americanus, and comparison with the commercial biocontrol agent Aphidoletes aphidimyza. Issue 5 (24th February 2022) - Ouattara, Téné Yacine; Fournier, Marc; Rojo, Santos; Lucas, Eric
Abstract: Aphids (Hemiptera: Aphididae) are a major economic problem in numerous crops, including pepper, melon, and potato. Larvae of the American hoverfly, Eupeodes americanus (Wiedemann) (Diptera: Syrphidae), are common aphidophagous natural enemies in agrosystems in North America. The objective of the present study was to characterize the development cycle of E. americanus in order to evaluate its potential as a biocontrol agent. The development cycle, survival rate, and adult longevity of E. americanus were determined and compared with those of the commercial aphid midge Aphidoletes aphidimyza (Rondani) (Diptera: Cecidomyiidae) under laboratory conditions, using the green peach aphid, Myzus persicae (Sulzer), as prey. The complete preimaginal development time, pupal development time, egg hatching rate, sex ratio, and survival rate were not different between E. americanus and the commercial A. aphidimyza . The larval developmental time was longer in the syrphid species, increasing the predation window. Finally, the adult longevity of the syrphid was drastically longer than that of A. aphidimyza . These results demonstrate a potential for E. americanus as a new aphidophagous biocontrol agent. Abstract : Larvae of Eupeodes americanus (Diptera: Syrphidae) are common natural enemies of aphids in natural systems and agrosystems in North America. In this study, the development cycle, survival rate, and adult longevity of E. americanus were determined and compared with those of the commercial aphid midge Aphidoletes aphidimyza (Diptera: Cecidomyiidae) under laboratory conditions, in order to evaluate its potential as a biocontrol agent. The results demonstrated a high potential for E. americanus .